Examining the Relationship Between Job Stress and Employee Turnover Intention - Ramadhanty, Nadyfa (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study investigates the complex relationship between job stress and turnover intention, highlighting the mixed findings in existing literature. While some research indicates a direct correlation between job stress and increased turnover intentions, other studies suggest that job stress may not always be the primary factor influencing an employee's decision to leave. This paper aims to provide a nuanced understanding of the conditions under which job stress leads to turnover, emphasizing the role of mediating and moderating factors such as organizational support and job satisfaction. Utilizing a library research methodology, the study systematically reviews existing literature and secondary data to identify key themes and insights. The findings underscore the necessity for organizations to implement effective strategies to support employee mental health and mitigate the adverse effects of job stress, ultimately fostering a more stable and productive workforce.